Blended Finance for Climate Resilience: A Bibliometric Analysis - Ari Purwanti; Paramita Andiani; Dila Padila Nurhasanah (West Science Social and Humanities Studies, 2026)
Climate change has intensified the need for innovative financing mechanisms capable of supporting resilience-building initiatives and addressing the substantial adaptation financing gap. Among these mechanisms, blended finance has emerged as a strategic approach that combines public, private, and philanthropic capital to mobilize investment for sustainable development and climate-related projects. Despite growing scholarly interest in blended finance and climate resilience, a comprehensive understanding of the intellectual structure and evolution of this research field remains limited. Therefore, this study aims to map the development, knowledge structure, and emerging trends of blended finance for climate resilience through a bibliometric analysis. Data were collected from the Scopus database using relevant search terms related to blended finance and climate resilience. The retrieved bibliographic records were analyzed using VOSviewer to examine publication trends, co-authorship networks, institutional and country collaborations, citation patterns, and keyword co-occurrence relationships. The findings reveal that blended finance, climate change, finance, investments, and climate finance constitute the core themes of the literature. Overlay visualization indicates a recent shift toward research on renewable energy, energy transitions, carbon markets, and decarbonization, reflecting the growing integration of climate resilience and sustainable investment agendas. Collaboration analysis highlights the prominent roles of the United Kingdom and the United States as major contributors to the field, while citation analysis identifies climate finance governance and sustainable transition financing as the most influential research streams. The study concludes that blended finance has evolved into a multidisciplinary research domain that plays a critical role in mobilizing resources for climate resilience and sustainable development. These findings provide valuable insights for researchers, policymakers, and investors seeking to advance innovative financing strategies for climate adaptation and resilience-building initiatives.